Assessing the Risk of Intracranial Aneurysm Rupture Using Morphological and Hemodynamic Biomarkers Evaluated from Magnetic Resonance Fluid Dynamics and Computational Fluid Dynamics - Perera, Roshani (Magn Reson Med Sci, 2020)
PURPOSE: Evaluate in vivo hemodynamic and morphological biomarkers of intracranial aneurysms, using magnetic resonance fluid dynamics (MRFD) and MR-based patient specific computational fluid dynamics (CFD) in order to assess the risk of rupture. METHODS: Forty-eight intracranial aneurysms (10 ruptured, 38 unruptured) were scrutinized for six morphological and 10 hemodynamic biomarkers. Morphological biomarkers were calculated based on 3D time-of-flight magnetic resonance angiography (3D TOF MRA) in MRFD analysis. Hemodynamic biomarkers were assessed using both MRFD and CFD analyses. MRFD was performed using 3D TOF MRA and 3D cine phase-contrast magnetic resonance imaging (3D cine PC MRI). CFD was performed utilizing patient specific inflow–outflow boundary conditions derived from 3D cine PC MRI. Univariate analysis was carried out to identify statistically significant biomarkers for aneurysm rupture and receiver operating characteristic (ROC) analysis was performed for the significant biomarkers. Binary logistic regression was performed to identify independent predictive biomarkers. RESULTS: Morphological biomarker analysis revealed that aneurysm size [P = 0.021], volume [P = 0.035] and size ratio [P = 0.039] were statistically significantly different between the two groups. In hemodynamic biomarker analysis, MRFD results indicated that ruptured aneurysms had higher oscillatory shear index (OSI) [OSI.max, P = 0.037] and higher relative residence time (RRT) [RRT.ave, P = 0.035] compared with unruptured aneurysms. Correspondingly CFD analysis demonstrated significant differences for both average and maximum OSI [OSI.ave, P = 0.008; OSI.max, P = 0.01] and maximum RRT [RRT.max, P = 0.045]. ROC analysis revealed AUC values greater than 0.7 for all significant biomarkers. Aneurysm volume [AUC, 0.718; 95% CI, 0.491–0.946] and average OSI obtained from CFD [AUC, 0.774; 95% CI, 0.586–0.961] were retained in the respective logistic regression models. CONCLUSION: Both morphological and hemodynamic biomarkers have significant influence on intracranial aneurysm rupture. Aneurysm size, volume, size ratio, OSI and RRT could be potential biomarkers to assess aneurysm rupture risk.